The cult of the Virgin Mary : psychological origins - Carroll, Michael P., 1944- (Book collections on Project MUSE., 1986)
Tracing devotion to Mary to psychological and historical processes that began in the fifth century, Michael Carroll answers intriguing questions: What explains the many reports of Marian apparitions over the centuries? Why is Mary both "Virgin" and "Mother" simultaneously? Why has the Marian cult always been stronger in certain geographical areas than in others? The first half of the book presents a psychoanalytic explanation for the most salient facts about the Marian cult and the second addresses the question of Marian apparitions.